Relevance of Lesson Plans with the Implementation of Islamic Education Learning in Vocational Schools - Hidayat, Wahyu; Muzakkir, Muzakkir; Fardi, Syamsu (Universitas Pesantren Tinggi Darul 'Ulum, 2020)
Lesson plans are an important thing that must be done before learning takes place. Lesson plans are very important because it can help make timely decisions and provide opportunities for easier control and monitoring in their implementation. This study aims to describe and analyze the relevance of lesson planning and implementation of learning in Islamic religious education subjects. This research was conducted at SMK Negeri I Parepare as a leading vocational school in Parepare. This research approach is descriptive qualitative. Collecting data using interviews, documentation and observation. The results showed that in preparing lesson plans at the SMK Negeri 1 Parepare, the teacher used the syllabus as a reference in making lesson plans. The internal relevance between the components in the lesson plans (Rencana Pelaksanaan Pembelajaraan/RPP) is interrelated. The external relevance between the lesson plans of Islamic religious education subjects at SMK Negeri 1 Parepare in the material of Muslim concern for bodies and wisdom and the benefits of organizing corpses is as follows: the material presented in class is relevant to what is in the RPP, time allocation used is relevant to what has been planned in the lesson plan, there are several learning activities process in the classroom that are not relevant to what was planned in the lesson plan, the assessment taken is relevant to what has been planned in the lesson plan.